2017
DOI: 10.4028/www.scientific.net/msf.899.353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sn and Cu on Corrosion Resistance of LaMgAlMnCoNi Type Alloys

Abstract: This paper reports the results of investigation carried out to evaluate the corrosion resistance of tin and copper in as-cast alloys represented by two sequential series, first: La0.7Mg0.3Al0.3Mn0.4Co0.5-xSnxNi3.8 (x = 0.0, 0.1, 0.2, 0.3 and 0.5) and second: La0.7Mg0.3Al0.3Mn0.4Sn0.5-yCuyNi3.8 (y = 0.0, 0.1, 0.2, 0.3 and 0.5). Electrochemical methods, specifically, polarization curves have been employed in this study. Copper substitution yielded good overall performance of the alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Later it was discovered that Y 2 O 3 incorporates into the continuous corrosion layer as Y(OH) 3 , reducing a driving force towards formation of Mm(OH) 3 , thus, reducing the corrosion rate of the electrode [18]. It was also found that substitution of cobalt with a more noble tin or copper decreases corrosion of the anodic material [19]. Recently, it was reported that substitution of La sites with nickel atoms can significantly enlarge the cycle lifetime of an anode, even up to 2415 cycles in comparison with the standard lifetime of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Later it was discovered that Y 2 O 3 incorporates into the continuous corrosion layer as Y(OH) 3 , reducing a driving force towards formation of Mm(OH) 3 , thus, reducing the corrosion rate of the electrode [18]. It was also found that substitution of cobalt with a more noble tin or copper decreases corrosion of the anodic material [19]. Recently, it was reported that substitution of La sites with nickel atoms can significantly enlarge the cycle lifetime of an anode, even up to 2415 cycles in comparison with the standard lifetime of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Till currently, the electrochemical and protected films of P355 Cs joining in alkaline high (pH > 12.5) and anoxic environs at more polarization had negative (-1.0 V-0 V) potential are scarcely examined [18][19][20]. So, it is very worth travelling the structure and goods of the hindrance film obtain on P355 Cs in this condition [21][22][23].…”
Section: Introduction mentioning
confidence: 99%